2005
DOI: 10.1001/archinte.165.9.978
|View full text |Cite
|
Sign up to set email alerts
|

Risk of Hospitalization for Myocardial Infarction Among Users of Rofecoxib, Celecoxib, and Other NSAIDs

Abstract: Current and new users of all classes of nonaspirin NSAIDs had elevated relative risk estimates for MI. Although the increased risk estimates may partly reflect unmeasured bias, they indicate the need for further examination of the cardiovascular safety of all nonaspirin NSAIDs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
165
3
8

Year Published

2006
2006
2011
2011

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 283 publications
(184 citation statements)
references
References 36 publications
8
165
3
8
Order By: Relevance
“…In a study by Choi et al, treatment with MTX provided substantial benefit in terms of reduction of cardiovascular mortality (6) and, although several proatherosclerotic effects of corticosteroids have been described, it has been suggested that their antiinflammatory effects may balance out their adverse cardiovascular effects, thus reducing the risk of accelerated atherosclerosis in corticosteroid-treated patients with RA (31). In a recent study, relative risk estimates for myocardial infarction were shown to be elevated among current and new users of all classes of non-aspirin NSAIDs (32). However, this finding has not been evaluated specifically in patients with RA.…”
Section: Discussionmentioning
confidence: 98%
“…In a study by Choi et al, treatment with MTX provided substantial benefit in terms of reduction of cardiovascular mortality (6) and, although several proatherosclerotic effects of corticosteroids have been described, it has been suggested that their antiinflammatory effects may balance out their adverse cardiovascular effects, thus reducing the risk of accelerated atherosclerosis in corticosteroid-treated patients with RA (31). In a recent study, relative risk estimates for myocardial infarction were shown to be elevated among current and new users of all classes of non-aspirin NSAIDs (32). However, this finding has not been evaluated specifically in patients with RA.…”
Section: Discussionmentioning
confidence: 98%
“…Two other epidemiologic studies also highlighted a potential cardiovascular risk of nonselective NSAID as well as COX-2 selective drugs. A study from Denmark reported that there was increased incidence of first-time hospitalization for myocardial infarction in patients who were taking all classes of nonaspirin NSAID (149), and an analysis of 468 practice groups in England reported an increased risk for myocardial infarction in patients who were taking either COX-2 selective or nonselective NSAID (150).…”
Section: Increased Cardiovascular Thrombotic Eventsmentioning
confidence: 99%
“…Certain medications used to treat IA and SLE may also contribute to the increased risk of CVD, including nonsteroidal anti-inflammatory drugs (NSAIDs) [20], COX-2 inhibitors [5,20], steroids [21,22], and anti-folate medications such as methotrexate [23,24].…”
Section: Introductionmentioning
confidence: 99%